A direct test of the buffer-stock model of saving - Tullio Jappelli; Mario Padula; Luigi Pistaferri (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
Recent models with liquidity constraints and impatience emphasize that consumers use savings to buffer income fluctuations. When wealth is below an optimal target, consumers try to increase their buffer stock of wealth by saving more. When it is above target, they increase consumption. This important implication of the buffer stock model of saving has not been subject to direct empirical testing. We derive from the model an appropriate theoretical restriction and test it using data on working-age individuals drawn from the 2002 and 2004 Italian Surveys of Household Income and Wealth. One of the most appealing features of the survey is that it has data on the amount of wealth held for precautionary purposes, which we interpret as target wealth in a buffer stock model. The test results do not support buffer stock behavior, even among population groups that are more likely, a priori, to display such behavior. The saving behavior of young households is instead consistent with models in which impatience, relative to prudence, is not as high as in buffer stock models.
urn:nbn:de:hebis:30-51001
Keywords: D91; 330; Buffer Stock Model; Precautionary Saving; Intertemporal Choice; Haushaltseinkommen; Lebenszyklus; Konjunktur; Vermögen; Sparen; Alterssicherung; Buffer-Stock-Ansatz; Italien